Elementary School Students' Talent Analysis Through Sparing Partners in Futsal Extracurricular Activities - Aang Solahudin Anwar; Sofyan Suari; Andes Safarandes Asmara; Anggy Giri Prawiyogi; Rifyan Triyana Putra (STAI Hubbulwathan Duri, 2023)
This research was motivated by the extracurricular talent in one elementary school in Karang Regency, which was still unable to compete with another elementary school at the District Level during the Sports and Art Events (Porseni) event. The purpose and objective of this research are to serve as a benchmark for improving the achievement of elementary school-level students in sports. This research was carried out by conducting sparring partners between fourth-grade students involved in extracurricular activities. The sport that is contested is futsal. The data analysis technique used in this research is descriptive qualitative. Data were collected by observing the activities carried out by students and conducting interviews with sports teachers and students who participate in futsal. Research results show that students are more enthusiastic, active, not lazy, and feel happy. Inter-class Sparing Partner activities at the elementary level can encourage students to be more active and stimulate them more to master the sport of futsal to develop their talents further and excel in the sport of futsal.